Digital transformation in the tourism sector of Ponorogo Regency, Indonesia - Moch Rifqi Mei Redha; Ulung Pribadi; Herpita Wahyuni (Jurnal Studi Komunikasi, 2025)
The Ponorogo Regency has various tourism destinations that comprises natural, artificial, and cultural sites. Digitalisation in this sector is needed to keep up with the times. This study investigated the factors that influence digital transformation in the tourism sector of Ponorogo Regency and identified variables that influence this transformation positively or negatively. This study used a quantitative methodology by distributing questionnaires online via Google Forms to 99 respondents in Ponorogo. The data processing used SEM-PLS software for data analysis and hypothesis testing. The study’s findings show that digital transformation in tourism is positively and significantly influenced by leadership, employee engagement, and the external environment through technological advancement. However, organisational culture, structure, communication methods, and resources do not positively or significantly impact the digital transformation of the tourism industry. These findings suggest that local governments should prioritise investments in leadership development, employee training, and delivering the latest technological innovations to implement digital transformation strategies effectively.